In-hospital and midterm post-discharge complications of adults hospitalised with respiratory syncytial virus infection in France, 2017–2019: an observational study. Issue 3 (3rd March 2022) - Descamps, Alexandre; Lenzi, Nezha; Galtier, Florence; Lainé, Fabrice; Lesieur, Zineb; Vanhems, Philippe; Amour, Sélilah; L'Honneur, Anne-Sophie; Fidouh, Nadhira; Foulongne, Vincent; Lagathu, Gisèle; Duval, Xavier; et al.
Objectives: The purpose of this study was to describe the clinical characteristics and in-hospital and post-discharge outcomes of respiratory syncytial virus (RSV) infection among adults hospitalised with influenza-like illness (ILI) and compared against patients admitted for influenza. Methods: Adults hospitalised with ILI were prospectively included from five French university hospitals over two consecutive winter seasons (2017/2018 and 2018/2019). RSV and influenza virus were detected by multiplex reverse transcription PCR on nasopharyngeal swabs. RSV-positive patients were compared to RSV-negative and influenza-positive hospitalised patients. Poisson regression models were used to estimate the adjusted prevalence ratio (aPR) associated with in-hospital and post-discharge outcomes between RSV and influenza infections. The in-hospital outcome was a composite of the occurrence of at least one complication, length of stay ≥7 days, intensive care unit admission, use of mechanical ventilation and in-hospital death. Post-discharge outcome included 30- and 90-day all-cause mortality and 90-day readmission rates. Results: Overall, 1428 hospitalised adults with ILI were included. RSV was detected in 8% (114 of 1428) and influenza virus in 31% (437 of 1428). Patients hospitalised with RSV were older than those with influenza (mean age 73.0 versus 68.8 years, p=0.015) with a higher frequency of chronic respiratory or cardiac disease (52% versus 39%, p=0.012, and 52% versus 41%, p=0.039, respectively) and longer hospitalisation duration (median stay 8 versus 6 days, p<0.001). Anti-influenza therapies were less prescribed among RSV patients than influenza patients (20% versus 66%, p<0.001). In-hospital composite outcome was poorer in RSV patients (aPR 1.5, 95% CI 1.1–2.1) than in those hospitalised with influenza. No difference was observed for the post-discharge composite outcome (aPR 1.1, 95% CI 0.8–1.6). Conclusion: RSV infection results in serious respiratory illness, with worse in-hospital outcomes than influenza and with similar midterm post-discharge outcomes. Respiratory syncytial virus infection in hospitalised adults with influenza-like illness was associated with poor in-hospital and midterm post-discharge outcomes, which may be worse than or similar to those of patients with influenza virus infection https://bit.ly/2VAsMhh